Comparative Efficacy and Safety of Antipsychotic Drugs for Tic Disorders: A Systematic Review and Bayesian Network Meta-Analysis - Yang, Chunsong; Hao, Zilong; Zhang, Ling-Li; Zhu, Cai-Rong; Zhu, Ping; Guo, Qin (Pharmacopsychiatry, 2019)
Objective The purpose of this study was to evaluate the efficacy and safety of antipsychotic drugs for tic disorders (TDs) in a network meta-analysis.Methods PubMed, Embase, Cochrane Library, and 4 Chinese databases were searched. Randomized controlled trials (RCTs) evaluating the efficacy of antipsychotic drugs for TDs were included.Results Sixty RCTs were included. In terms of tic symptom score, compared with placebo, haloperidol, risperidone, aripiprazole, quetiapine, olanzapine, and ziprasidone can significantly improve tic symptom score (standardized mean differences [SMD] ranged from −12.32 to −3.20). Quetiapine was superior to haloperidol, pimozide, risperidone, tiapride, aripiprazole, and penfluridol for improving tic symptom score (SMD ranged from −28.24 to −7.59). Compared with tiapride, aripiprazole could significantly improve tic symptom score (SMD=−4.27). Compared with all other drugs, penfluridol was not effective. Atypical antipsychotics were generally well tolerated.Conclusions Atypical antipsychotics (risperidone and aripiprazole) appear to be the most robust evidence-based options for the treatment of TDs. Quetiapine may be a promising therapy. Ziprasidone and olanzapine are also effective, but the evidence is lacking. Further high-quality directly comparing different pharmacological treatment studies are justified.
Keywords: tic disorder; antipsychotic drug; systematic review; network meta-analysis